PENGARUH PROMOSI, HARGA, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN: Studi Pada PT. Bumen Redja Abadi Mitsubishi Sidoarjo - Damayanti, Dila; Wahyuningtyas, Yunita Fitri; Merdiana, Candra Vionela (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
This study's goal is to ascertain the degree to which PT. BUMEN REDJA ABADI (MITSUBISHI SIDOARJO)'s promotions, prices, and service quality affect customers' decisions to buy. Quantitative explanatory research is the methodology employed. Customers of PT. BUMEN REDJA ABADI (MITSUBISHI SIDOARJO) were given questionnaires, which produced the processed data. Multiple linear regression is the data analysis method employed in this investigation. The validity test, reliability test, and partial T test are used to analyze the study description in relation to the hypothesis. The promotion variable (X1), price (X2), and quality (X3) have a partial and substantial beneficial impact on consumer purchase decisions at PT. BUMEN REDJA ABADI (MITSUBISHI SIDOARJO), according to the findings of data analysis for the significance test (t test).